Penggunaan Bahasa Pemrograman Python dalam Menganalisis Perbedaan Desain Website Tren di Negara Jepang dan Dunia - Avelino, Dionisius; Cancerlon, Lawrance; Ryanta, M. Kenny; Christianto, Yonathan Henry; Wangnardy, Weslie (Universitas Labuhanbatu, 2022)
The use of the internet in the digital age is common with almost all information that can be accessed through web pages. The form of design of a web page is a major concern when accessing information. The design of the Japanese web page is a concern in this study which aims to analyze the differences in design with other countries ' web pages. Research using this qualitative method is done by analyzing the Python programming language in the creation of web pages. Analysis of web pages from Japan begins with data collection, then data processing, and ends with analyzing the data. The results showed that there is a tendency to differences in the Japanese character writing system, cultural differences, technology developed by the older generation, and slow adoption of new technology. So Japanese web pages tend to look different from other countries.